BRAIN NEOPLASMS IN PATIENTS WITH CEREBROVASCULAR DISEASES. - Daniela Arabadzhieva; Ara G. Kaprelyan; Nevena Radeva (Peytchinski Publishing, 2015)
There is recent evidence of co-occurrence of benign and malignant brain tumours and cerebrovascular disorders in the same patients. The present concise review analyzes the newly-published foreign literature on this actual topic. The epidemiological investigations reveal an association between the acute ischaemic and haemorrhagic stroke, on the one hand, and some common cerebral neoplasms, on the other hand. The role of modern thrombolytic therapy in such patients is outlined. The risks of chemotherapy and radiotherapy for the development of stroke should be taken into consideration. A series of interesting rare cases illustrating the diagnostic and therapeutic opportunities in the patients presenting with simultaneous or consecutive common cerebral neoplasms and stroke proves the necessity of careful diagnosis and timely management of these patients in the routine clinical practice.